TINJAUAN KRIMINOLOGI TINDAK PIDANA PENCURIAN DENGAN KEKERASAN "BEGAL" Di KOTA BEKASI (STUDI DI POLRES BEKASI) - Dwi Fernando Marbun, (2023)
Crime will continue to increase in different ways, even with increasingly sophisticated and modern equipment, so that crime will increasingly disturb today's society. One of the crimes that often occurs in society is the crime of robbery. In the Criminal Code (KUHP), robbery is regulated in Article 365, which deals with theft accompanied by violence. In this study, researchers used a type of qualitative research using an empirical approach. Empirical juridical research, also known as field research, examines the legal provisions that apply and what actually happens in society. The purpose of this research is to find out the factors that cause the occurrence of robbery, the efforts and also the obstacles encountered in tackling the crime of theft with violence "mugger" in the city of Bekasi. Whereas the factors causing the occurrence of theft with violence, especially in the city of Bekasi, are recidivist factors, economic factors, environment, education and drug factors. Efforts made by law enforcement officials are preventive and repressive efforts. Preventive efforts carried out by the police are patrolling, checking (sweeping), installing CCTV and also conducting outreach to the community to prevent robbery or the crime of theft by force. Repressive efforts are taking action against perpetrators of robbery crimes through a criminal justice process and providing guidance in correctional institutions and the obstacles faced by the Polres Metro Bekasi City Police in tackling robbery crimes there are three obstacles, namely difficulties in identifying perpetrators, different modes of crime, and the lack of community participation in eradicating and dealing with robbery crimes.